Article RETRACTED due to manipulation by the authors Fitness Levels of Elementary School Students Based on Gender and Race in Indonesia: Are There Differences? - Widiyanto Widiyanto; Hendra Setyawan; Suharjana Suharjana; Sugeng Purwanto; Eka Novita Indra; Sujarwo Sujarwo; Sandi Prayudho; José Vicente García-Jiménez; Ratko Pavlovic; Özgür Eken; Nuridin Widya Pranoto; Arief Darmawan; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aimed to determine differences in physical fitness levels based on Race and Gender in Indonesia. It used a comparative quantitative approach. The samples in this research were elementary school students in three provinces: Sumsel, DIY, and NTT. They were selected using cluster random sampling and yielded 254 people. Then, the samples were clustered to equalize numbers based on students’ gender and regional race (South Sumatra, DIY, & NTT). After this process, the remaining 132 people were taken. Students’ physical fitness data were collected using the Indonesian Physical Fitness Test (TKJI). The data were then analyzed using the parametric Two-Way ANOVA statistics. The results of the Two-Way ANOVA test showed that the race factor variable had a value of Sig. 0.00 < 0.05. This value indicates a significant difference in the TKJI test scores between races in the three provinces: South Sumatra, DIY, and NTT. In the gender factor variable, the Sig. 0.001 < 0.05, meaning a significant difference was also found in the TKJI test scores between male and female students. Furthermore, for the combined race and gender factor variables, the Sig 0.485 > 0.05. Since the Sig value was greater, there is no influence or interaction between the race and gender factors in the three provinces in determining the results of the students' TKJI scores. Differences in physical fitness in terms of race can be caused by differences in physical activity, socioeconomic status, and social factors, such as racial discrimination and interpersonal racial discrimination. These differences can manifest as emotional stress due to increased psychological stress and increased risk of unhealthy behavior, including activities. In addition, the difference in physical fitness was also found between genders. The results show that men have a better level of physical fitness than women. One of the reasons is possibly due to increased fat mass associated with growth and puberty in girls. In addition, boys are often more active than girls.